Penggunaan Glyroxyl untuk Menghambat Penurunan Mutu Ikan Mas (Cyprinus carpio) Segar - Farida Ariyani; Jovita Tri Murtini; Ninoek Indriati; Dwiyitno Dwiyitno; Yusma Yenni (Universitas Gadjah Mada, 2007)
One of the preservative agents that was claimed having bactericidal effect is glyroxyl. This study was aimed to observe the effect of glyroxyl on carp’s (Cyprinus carpio) shelf life. Factorial design was used in this experiment with 9 treatments in triplicates. The fish was immersed in glyroxyl solution at concentrations of 0 (control), 0.1, 0.3 and 0.5% (w/v) for 5 min. Following immersion, fish was drained and kept in plastic bucket at ambient temperature. Sampling was done at 0, 12 and 24 h storage and analysis was carried out organoleptically, chemically (TVB) and microbiologically (TPC, Enterobacter). Results showed that organoleptically, chemically and microbiologically, there were no significant different on spoilage inhibition of glyroxyl compared to control. Similar to control, glyroxyl was able to prevent spoilage of carp fish only up to 12 h. The fish was rejected by panelists after 12 h of storage. The TVB value and bacterial counts, including Enterobacter, also increased sharply after that time.